Design of A Half Ton dehydrator for Fish - Swaminath, M (Fishery Technology, 1964)
A half-ton capacity artificial dryer has been designed at the Central Institute of Fisheries Technology for drying fish like Mackerel, Sardine. White Bait etc. The dryer is a hot air re-circulation type. 80K. W. thermostatically controlled heatingcoils are made use of for heating the air. The air is circulated by means of an axial flow pattern fan. Drying takes place at a temp. of 115°F. The structure of the dryer to be made of Anjili wood. The cost of one dryer comes to about Rs. 20,000/-